Implementasi Budaya Sunda: Upaya Pelestarian Kaulinan Barudak di SMA Yadika Soreang - Hasya Inggriani Azahra; Naila Aurhelia F.M; Putri Shyarsheina Azzahra; Rima Irmayanti (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to determine how the implementation of Sundanese cultural values at Yadika Soreang High School. In this research using interview methods, and collecting data from the library via the internet which aims to identify the types of kaulinan barudak that exist and the types of kaulinan barudak that are preserved at Yadika Soreang High School, and also identify the values contained in kaulinan barudak The respondent of this research is the founder and manager of the Traditional Sports extracurricular at Yadika Soreang High School. The results of the study show that there are 7 kaulinan barudak that are preserved in the form of extracurricular Traditional Sports by SMA Yadika Soreang, each game has life values that are applied based on the values of silih asih, silih asah, and silih asuh. The values in the game are togetherness, leadership, honesty, spaciousness, and simplicity.